Effects of ageing treatment on corrosion behavior of 7075 aluminum alloy coated by micro arc oxidation (MAO). (1st May 2022) - Qi, Xing; Jiang, Bo; Song, Renguo
Abstract: The effects of ageing treatment on corrosion behavior of 7075 aluminum alloy coated by MAO have been investigated. The results suggest that precipitates (GPI, GP II zones, η and η') formed after ageing play a significant role on the thickness, porosity and corrosion resistance of MAO coating. After MAO coating is deteriorated during corrosion test, TEM observations show that coarse and discontinuously distributed precipitates at grain boundary contribute to the electrochemical corrosion resistance. HAADF-STEM images and EDS maps exhibit that the Mg segregation at grain boundary decreases with increasing the ageing time which reduces the stress corrosion cracking (SCC) susceptibility. Highlights: There are two ageing hardening peaks appearing at 36 h and 128 h respectively during long time ageing. Ageing treatment will affect the MAO coating properties as the electrical conductivity of specimens changed by ageing. Thicker and less porous MAO coating combined with less Mg segregation at grain boundary shows great SCC resistance.